Facile amidinations of 2-aminophenylboronic acid promoted by boronate ester formation. Issue 4 (10th January 2019) - Pappin, Brighid B.; Garget, Taylor A.; Healy, Peter C.; Simone, Michela I.; Kiefel, Milton J.; Houston, Todd A.
Abstract : Amidine synthesis by amine addition to nitriles normally requires high temperatures or harsh catalysts. Abstract : Amidine synthesis by amine addition to nitriles normally requires high temperatures or harsh catalysts. Here, we report that boronate esters can facilitate amidination of proximal amines with moderate heating. With amidines present in a number of drugs and the synthetic handle provided by the boron, this chemistry should find useful applications.